Financial conditions and monetary policy in Uruguay: An MS-VAR approach - Elizabeth Bucacos Iguini (Inter-American Development Bank (IDB), 2017)
This study analyzes the effects of "financial stress" on the Uruguayan macroeconomy in the 1998Q3-2016Q2 period with the underlying idea that financial shocks propagate differently during "normal times" than during times of "stress." This behavior is captured in a multivariate framework through a Markovswitching vector auto regressive (MS-VAR) model. The evidence found so far supports the idea that financial conditions affect the macroeconomy, as they not only change the private investment long-run average growth rate but also directly modify the behavior of monetary policy.
Keywords: C34; E27; E44; E62; 330; Switching-regression models; Investment; Financial markets and the macroeconomy; Uruguay